DIGITALISASI LAYANAN INFORMASI DESA MELALUI PENGEMBANGAN WEBSITE UNTUK MENINGKATKAN PROMOSI UMKM DAN POTENSI WISATA DESA KOTA GURING - Rahayu, Sri; Pratama, Rizki Mupty; Sasmita, Rika Febri; Ramadhan, Doni; Herlambang, Dian; Helmita, Helmita (LPPM Universitas Widya Dharma Klaten, 2026)
Kota Guring Village possesses diverse economic and tourism potential, yet faces challenges in promoting its assets due to limited access to digital media. This community service program aims to support the digital transformation of village information services through the development of a website using the Google Sites platform. The objective is to enhance the visibility of local MSMEs and tourism destinations. The implementation involved five stages: (1) coordination and needs assessment with village officials; (2) data collection on four MSMEs (Dapoer Akmal, Kopi Lampung, Virgin Coconut Oil, and Jamil Donuts Kalianda) and two tourism sites (Guring Beach and Way Guyuran); (3) website structure and content design; (4) website development and optimization; and (5) training for village staff on website management. The resulting website features a village profile, MSME catalog with contact information, tourism gallery, and a communication form. It provides 24/7 access to village information, offers free digital promotion for MSME actors, and increases the visibility of local tourism to potential visitors. This initiative contributes to sustainable village development by integrating information technology into public service delivery and economic empowerment.